Behavioral Changes in Children After Emergency Department Procedural Sedation. (13th November 2017) - Pearce, Jean I.; Brousseau, David C.; Yan, Ke; Hainsworth, Keri R.; Hoffmann, Raymond G.; Drendel, Amy L.
Abstract: Objective: The purpose of this study was to determine the proportion of children undergoing procedural sedation for fracture reduction in the emergency department (ED) observed to experience negative postdischarge behaviors. Predictors of negative behaviors were evaluated, including anxiety. Methods: This was a prospective cohort study of children receiving intravenous ketamine sedation for ED fracture reduction. The child's anxiety prior to sedation was measured with the Modified Yale Preoperative Anxiety Scale. Negative behavioral changes were measured with the Post‐Hospitalization Behavior Questionnaire 1 to 2 weeks after discharge. Descriptive statistics and odds ratios (ORs) were calculated. Chi‐square test was used for comparisons between groups. Multivariable logistic regression models evaluated predictors of negative behavioral change after discharge. Results: Ninety‐seven patients were enrolled; 82 (85%) completed follow‐up. Overall, 33 (40%) children were observed to be highly anxious presedation and 18 (22%) had significant negative behavior changes after ED discharge. Independent predictors for negative behaviors were high anxiety (OR = 9.0, 95% confidence interval [CI] = 2.3–35.7) and nonwhite race (OR = 6.5, 95% CI = 1.7–25.0). Conclusion: For children undergoing procedural sedation in the ED, two in five children have high preprocedure anxiety and almost one in four have significant negative behaviors 1 to 2 weeks after discharge. Highly anxious and nonwhite children have increased risk of negative behavioral changes that have not been previously recognized in the ED setting.